ANALYSIS OF IL6 GENE POLYMORPHISM (rs1800795) IN HEMORRHAGIC VASCULITIS - D. S. Matkarimova; S.SH. Yunusova; U.I. Solijonova; N.D. Erdanova (Modern American Journals, 2025)
Objective. To investigate allelic polymorphism of the IL6 gene (rs1800795) in patients with immune microthrombotic vasculitis (hemorrhagic vasculitis).Materials and Methods. The study included 75 patients with hemorrhagic vasculitis (age range: 16–80 years) and 73 conditionally healthy controls without hemostatic system pathology, matched by age. Detection of the IL6 polymorphism (rs1800795) was performed using SNP-PCR.Results and Conclusions. Carriage of the IL6 gene polymorphism (rs1800795) was not associated with increased risk for hemorrhagic vasculitis.
Keywords: IL6 gene polymorphism (rs1800795), hemorrhagic vasculitis, allele, genotype, association, risk.